Kinetics of foot-and-mouth disease vaccine-induced antibody responses in buffaloes (Bubalus bubalis): avidity ELISA as an alternative to the virus neutralization test - Sala, Juan Manuel; Mansilla, Florencia Celeste; Miraglia, Maria Cruz; Caspe, Sergio Gaston; Perez Filgueira, Daniel Mariano; Capozzo, Alejandra (Frontiers Media, 2024)
The role of water buffaloes in foot-and-mouth disease (FMD) epidemiology as one of the major hosts of the virus that can develop persistent asymptomatic infection highlights the importance of sustaining surveillance on the antibody response elicited by vaccination in these animals. There is gap in the knowledge on how serological assays that measure antibodies against capsid proteins perform with buffalo samples and which would be the most reliable test to substitute the virus neutralization test (VNT) a cumbersome and low-throughput tool for field surveillance. Alternatively, the liquid-phase blocking sandwich ELISA (LPBE) is commonly used. Previous data from our laboratory demonstrated that the vaccine-induced antibodies assessed by the LPBE yielded low specificity with buffaloes’ samples. In contrast, a single-dilution avidity ELISA (AE) aimed to detect high-avidity antibodies against exposed epitopes, combined with an indirect ELISA (IE) to assess IgG levels, produced more reliable results. Here we analyzed for the first time the kinetics of the antibodies induced by vaccination in two different buffalo herds (n = 91) over 120 days using AE, IE, LPBE, and the VNT. Kinetics were similar in the different assays, with an increase of antibodies between 0- and 14-days post-vaccination (dpv) which were maintained thereafter. VNT and AE results were concordant (Kappa value = 0.76), and both assays revealed a decay in the antibody response in calves with maternal antibodies at 90 and 120 dpv, which was not evidenced by the LPBE. These results show that kinetics of antibody responses to FMD vaccination are similar in buffalo and cattle, and support the use of indirect ELISA assays, in particular Avidity ELISA, as alternatives to the VNT for vaccine-immunity monitoring irrespectively of the animal’s passive or active immune status.